1992
DOI: 10.1002/jmri.1880020409
|View full text |Cite
|
Sign up to set email alerts
|

Effect of perfusion on exercised muscle: MR imaging evaluation

Abstract: An ischemic clamp model of exercise was used to evaluate the potential role of blood flow in mediating changes in the magnetic resonance imaging appearance of skeletal muscle. Proton relaxation times of muscle were serially estimated in 10 healthy subjects (a) before exercise, (b) after exercise in the presence of vascular occlusion (VO1), (c) during vascular reocclusion after 1 minute of reperfusion (VO2), and (d) after reinstitution of continuous flow. T1 and T2 of active muscles were increased during VO1. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 20 publications
2
38
0
Order By: Relevance
“…We conclude that changes in extramuscular influences, such as blood flow, are necessary for the decreases in R 1 associated with exercise. This conclusion is consistent with the findings of Archer et al (28) that maximum changes in R 1 require blood flow to the active muscles, and that reactive hyperemia following suprasystolic application of a blood pressure cuff can decrease the R 1 of inactive muscles.…”
Section: The R 2 Decrease During Exercise Occurs Independently Of R 1supporting
confidence: 92%
“…We conclude that changes in extramuscular influences, such as blood flow, are necessary for the decreases in R 1 associated with exercise. This conclusion is consistent with the findings of Archer et al (28) that maximum changes in R 1 require blood flow to the active muscles, and that reactive hyperemia following suprasystolic application of a blood pressure cuff can decrease the R 1 of inactive muscles.…”
Section: The R 2 Decrease During Exercise Occurs Independently Of R 1supporting
confidence: 92%
“…Previous studies demonstrated that the increase in T 2 after exercise occurred in the presence of vascular occlusion. 20,21 The increase in extra-cellular fluid was one of the most important factors involved.…”
Section: Discussionmentioning
confidence: 99%
“…1 H-magnetic resonance (MR) imaging can be used to estimate the activity of superˆcial and deep muscles, and MR imaging can document changes produced by exercise in human muscle tissue. [1][2][3][4][5][6][7][8] In contrast to non-exercising tissues, muscles used during exercise appear hyperintense, and this hyperintensity declines during recovery. Exercised-induced changes in signal primarily result from increases in the transverse relaxation time (T 2 ) of tissue caused by changes in water content and are most pronounced on T 2 -weighted images.…”
Section: Introductionmentioning
confidence: 99%